Women and the Universal Declaration of Human Rights - Adami, Rebecca (Taylor & Francis, 2025)
Who were the non-Western women delegates who took part in the drafting of the United Nations Charter and the Universal Declaration of Human Rights (UDHR) from 1945-1948? Which member states did these women represent, and in what ways did they push for a more inclusive language than "the rights of Man" in the texts? This book provides a gendered historical narrative of human rights from the San Francisco Conference in 1945 to the final vote of the UDHR in the United Nations General Assembly in December 1948. It highlights the contributions by Latin American feminist delegates, and the prominent non-Western female representatives from new member states of the UN.